2020
DOI: 10.1080/15476286.2020.1723328
|View full text |Cite
|
Sign up to set email alerts
|

Identification of RNA 3´ ends and termination sites in Haloferax volcanii

Abstract: Archaeal genomes are densely packed; thus, correct transcription termination is an important factor for orchestrated gene expression. A systematic analysis of RNA 3´termini, to identify transcription termination sites (TTS) using RNAseq data has hitherto only been performed in two archaea, Methanosarcina mazei and Sulfolobus acidocaldarius. In this study, only regions directly downstream of annotated genes were analysed, and thus, only part of the genome had been investigated. Here, we developed a novel algori… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…Term-seq analysis determines a terminator motif of two consecutive uridine-tracts in transcripts of M. maripaludis (Figure 4A ). Similar, but slightly different, uridine-rich motifs have also been observed in three representative Euryarchaeota and Crenarchaeota species, M.mazei , S.acidocaldarius ( 13 ) and H.volcanii ( 24 ). Uridine-rich sequences were considered as the intrinsic termination signal based on the earlier and primarily in vitro studies ( 18 , 19 , 22 ), however, whether this sequence merely pauses or also dismantles aRNAP for termination has not been clarified.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Term-seq analysis determines a terminator motif of two consecutive uridine-tracts in transcripts of M. maripaludis (Figure 4A ). Similar, but slightly different, uridine-rich motifs have also been observed in three representative Euryarchaeota and Crenarchaeota species, M.mazei , S.acidocaldarius ( 13 ) and H.volcanii ( 24 ). Uridine-rich sequences were considered as the intrinsic termination signal based on the earlier and primarily in vitro studies ( 18 , 19 , 22 ), however, whether this sequence merely pauses or also dismantles aRNAP for termination has not been clarified.…”
Section: Discussionsupporting
confidence: 66%
“…Earlier studies on individual genes have revealed that Archaea possess a bacteria-like but distinct intrinsic termination mode, by depending merely on a short uridine-rich sequence but not strictly requiring an upstream hairpin structure ( 1 , 18–22 ). Recently, the genome-level 3′-ends sequencing (Term-seq) analyses on three representative archaeal species, Methanosarcina mazei , Sulfolobus acidocaldarius and Haloferax volcanii , have identified similar over-representative uridine-rich tracts and without preceding hairpin structures in the transcripts 3′-ends ( 23 , 24 ). Term-seq also identified the eukaryotic-like alternative 3′-untranslated regions (3′-UTRs) in Archaea that are generated by consecutive termination sites, implying that Archaea could employ eukaryotic-like transcription termination modes and may also employ trans-acting (termination) factors ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Haloferax volcanii encodes an RNA splicing endonuclease (HVO_2952, endA) in a bicistronic operon together with a tryptophanyl-tRNA synthetase (HVO_2951, trpS1) (Figure 3), the two genes overlap by four nucleotides. Both the prokaryotic operon database (Taboada et al, 2012) and our transcriptome (Berkemer et al, 2020), TSS (Babski et al, 2016) and transcription termination site (TTS) data (Berkemer et al, 2020) confirm this genomic organization. According to our TSS studies (Babski et al, 2016), the gene for the splicing endonuclease seems to contain two promoters for the downstream trpS1 gene (Figure 3), therefore the trpS1 gene could be transcribed independently from the endA gene.…”
Section: Rna Splicing Endonuclease From Haloferax Volcaniisupporting
confidence: 67%
“…The expression of trpS1 can be regulated from two promoters located in the endA ORF which allows regulation of trpS1 expression independent of endA expression. This setup is another example of the independent regulation of genes that are part of the same operon (Berkemer et al, 2020). Seven circRNAs were identified by in silico analysis to be flanked by a BHB motif with a folding energy lower than −9.…”
Section: Enda/trps1 Operon Structurementioning
confidence: 99%
“…Lastly, the transcription termination pathway might be decisive whether TTC can occur, or vice versa ( Figure 2I ). In archaea, transcription terminates via two mechanisms that are not necessarily mutually exclusive: (i) intrinsic termination at poly(U) stretches ( Santangelo and Reeve, 2006 ; Hirtreiter et al, 2009 , 2010 ; Santangelo et al, 2009 ; Dar et al, 2016 ; Berkemer et al, 2020 ) or (ii) factor-dependent termination assisted by the archaeal termination factor aCPSF1/FttA that binds the nascent RNA ( Sanders et al, 2020 ; Yue et al, 2020 ). Importantly, aCPSF1 also enhances termination at poly(U) stretches.…”
Section: Co-transcriptional Processes and Transcriptomic Features Affecting Transcription-translation Coupling In Archaeamentioning
confidence: 99%